Dispensasi Nikah sebagai Syarat Bebas dalam Perkara Pidana Anak - Arief Wardhana; Lilik Andar Yuni (CV. Creative Tugu Pena, 2024)
This study discusses marriage dispensation as a condition for release in child criminal cases. Marriage dispensation is a permit granted by the court to couples who wish to marry under the age specified by law. In the context of child criminal cases, marriage dispensation is often proposed as an effort to avoid criminal penalties for children involved in cases of extramarital pregnancy. This study uses an empirical legal research method (qualitative research), namely a research method that is used together to obtain accurate, valid, reliable, and objective results with an empirical-normative research system. Data analysis is carried out by reviewing and interpreting the data received to obtain a deep understanding of the practice of marriage dispensation in child criminal cases. This study aims to analyze the legal implications of marriage dispensation in child criminal cases and to understand the judge's considerations in granting the dispensation.